2002
DOI: 10.1002/rcm.634
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionisation and ion‐trap fragmentation of substituted 3,4‐dihydro‐2(1H)‐pyridin‐2‐ones

Abstract: A variety of 5-alkoxycarbonyl-4-aryl-6-methyl-3,4-dihydro-2(1H)-pyridones and hexahydrofuro[3,4-b]-2(1H)-pyridones have been investigated by electron impact (EI) and electrospray ionisation (ESI) techniques. Sequential product ion fragmentation (MS(n)) was performed to elucidate the degradation pathways for these compounds. Comparisons are made between positive and negative even-electron ions from ESI spectra and the molecular radical cations obtained under EI conditions. The data collected in this paper provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…The final products IIIa–i were characterized by melting point, NMR and mass spectral data. Most compounds synthesized in this study were known and their spectral characterization showed satisfactory agreement with the previous literature data [ 33 , 34 , 35 ]. The 1 H-NMR spectra of DHP derivatives IIIa–i showed one singlet corresponding to the NH at δ ~ 10.7–11.3 ppm.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The final products IIIa–i were characterized by melting point, NMR and mass spectral data. Most compounds synthesized in this study were known and their spectral characterization showed satisfactory agreement with the previous literature data [ 33 , 34 , 35 ]. The 1 H-NMR spectra of DHP derivatives IIIa–i showed one singlet corresponding to the NH at δ ~ 10.7–11.3 ppm.…”
Section: Resultssupporting
confidence: 89%
“…In all cases, the MWAS yields for these compounds (Method A) were higher than those achieved previously with conventional synthesis conditions [ 33 , 34 , 35 ]. Moreover, the time of reaction was dramatically reduced from 12 h (720 min) in the conventional synthesis (Method B) to 10 min for the MWAS method.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…17 We have also reported the mass spectrometric behaviour of substituted 3,4-dihydro-2(1H)-pyridin-2-ones by electrospray ionization and ion-trap fragmentation methods. 18 This paper reports the complete 1 H and 13 C NMR assignments of a series of differently substituted 5-alkoxycarbonyl (1 and 2), 5-acetyl-4-aryl-3,4-dihydro-6-methyl-2(1H)pyridones (3) and pyridine derivatives 4 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%